Pengaruh Self- Esteem, Employability Skills, Dan Soft Skills Terhadap Kesiapan Kerja Siswa SMK: Studi Kasus Pada Siswa Kelas XII SMK Al-Ihsan Jakarta Barat - Kristanto, Dwi; Naomi, Mika Faustina; Aris Wahyu Kuncoro; Pakpahan, Maruji (Pusat Riset dan Inovasi Nasional, 2026)
The primary role of Vocational High Schools (SMK) in producing a workforce ready for work is often hampered by students' low mental readiness and competency. This study was conducted to evaluate the influence of self-esteem, technical work skills, and soft skills on the level of work readiness of 12th-grade students at SMK Al-Ihsan, West Jakarta. A sample of 123 respondents was selected using probability sampling techniques from a population of 178 respondents. Data processing was performed using multiple linear regression analysis with the assistance of SPSS version 27. The results of the study partially indicate that self-esteem and technical work skills have a positive and significant effect on work readiness. Conversely, soft skills were found to have no significant effect on work readiness among 12th-grade students at SMK Al-Ihsan, West Jakarta. These findings indicate that self-esteem and technical work skills are key factors in building student work readiness. Schools are recommended to continue optimizing the development of students' character and communication skills to minimize competency gaps when entering the workforce.